2007
DOI: 10.1074/jbc.m609842200
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochrome Blue Light Photoreceptors Are Activated through Interconversion of Flavin Redox States

Abstract: Cryptochromes are blue light-sensing photoreceptors found in plants, animals, and humans. They are known to play key roles in the regulation of the circadian clock and in development. However, despite striking structural similarities to photolyase DNA repair enzymes, cryptochromes do not repair double-stranded DNA, and their mechanism of action is unknown. Recently, a blue light-dependent intramolecular electron transfer to the excited state flavin was characterized and proposed as the primary mechanism of lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
504
4
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 384 publications
(532 citation statements)
references
References 49 publications
20
504
4
4
Order By: Relevance
“…k D >> k F and hence E >> 1). It has been suggested that the signalling state of the putative cryptochrome magnetosensor contains FAD that is either singly reduced (FAD  or FADH  ) 61 or, after further photoexcitation, fully reduced (FADH  ) 12,13 . Either way, rapid reduction of the donor-radical would stabilise the signalling state against reverse electron transfer so promoting signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…k D >> k F and hence E >> 1). It has been suggested that the signalling state of the putative cryptochrome magnetosensor contains FAD that is either singly reduced (FAD  or FADH  ) 61 or, after further photoexcitation, fully reduced (FADH  ) 12,13 . Either way, rapid reduction of the donor-radical would stabilise the signalling state against reverse electron transfer so promoting signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…3 Polyclonal antibody used for cry2 detection has been raised to the C-terminal domain as used previously. 6 …”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…In contrast, as will be discussed below, some studies have suggested that photoinduced electron 126 ÖZTÜRK ET AL. transfer is the key photophysical event in the CRY photocycle (Zeugner et al 2005;Banerjee et al 2007;Bouly et al 2007). …”
Section: The "Trp Triad" and Photoreductionmentioning
confidence: 99%
“…Most of these studies have been done on Arabidopsis CRYs. First, it has been reported that AtCRY1 and AtCRY2 made in insect cells contain flavin in the FAD ox state and that exposure of the insect cells expressing the CRYs to blue light reduces the FAD ox to a FADH°neutral radical (Banerjee et al 2007;Bouly et al 2007). This was complemented by in vitro experiments that demonstrated that exposure of AtCRYs to light followed by a dark phase under aerobic conditions cause the following transitions:…”
Section: Functional Properties Of Animal Cryptochrome Cryptochrome Phmentioning
confidence: 99%